2017
DOI: 10.1016/j.jconrel.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged inhibition of inflammation in osteoarthritis by triamcinolone acetonide released from a polyester amide microsphere platform

Abstract: Controlled biomaterial-based corticosteroid release might circumvent multiple injections and the accompanying risks, such as hormone imbalance and muscle weakness, in osteoarthritic (OA) patients. For this purpose, microspheres were prepared from an amino acid-based polyester amide (PEA) platform and loaded with triamcinolone acetonide (TAA). TAA loaded microspheres were shown to release TAA for over 60days in PBS. Furthermore, the bioactivity lasted at least 28days, demonstrated by a 80-95% inhibition of PGE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 57 publications
3
59
0
Order By: Relevance
“…In rodent models commonly used in the first stage of preclinical development of novel therapies, synovial fluid sampling over time is impossible and very small quantities of plasma are available for analysis. In the current study, plasma TAA levels in the first 2 days reflected the initial burst release of TAA‐loaded PEA occurring in vitro (Rudnik‐Jansen et al, ). The area under the curve (AUC) of the plasma levels, indirectly showing loss from the synovial cavity and hence delivery by the MSs, was approximately 10 times smaller for the MS‐based versus the bolus formulation of 0.7‐mg TAA.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…In rodent models commonly used in the first stage of preclinical development of novel therapies, synovial fluid sampling over time is impossible and very small quantities of plasma are available for analysis. In the current study, plasma TAA levels in the first 2 days reflected the initial burst release of TAA‐loaded PEA occurring in vitro (Rudnik‐Jansen et al, ). The area under the curve (AUC) of the plasma levels, indirectly showing loss from the synovial cavity and hence delivery by the MSs, was approximately 10 times smaller for the MS‐based versus the bolus formulation of 0.7‐mg TAA.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, the IA release of a dose of 60‐mg TAA from a PLGA MS platform, equivalent to the lowest dosage used in the current study, was shown to be safe in knee OA patients (Bodick et al, ). Also in a different, collagenase‐induced, rat model of OA, the extended release of TAA by PEA MSs did not show any effects on cartilage integrity nor induced tissue calcification (Rudnik‐Jansen et al, ). Given the absence of effects in previous studies of unloaded PEA MSs in OA animals, the MS platform per se is not likely to have contributed to the effects found either (Janssen et al, ; Rudnik‐Jansen et al, ), nor would have their combination with TAA bolus, given the absence of effects of either when administered separately.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations